Surveillance for yellow Fever virus in non-human primates in southern Brazil, 2001-2011: a tool for prioritizing human populations for vaccination. - Marco A B Almeida; Jader da C Cardoso; Edmilson Dos Santos; Daltro F da Fonseca; Laura L Cruz; Fernando J C Faraco; Marilina A Bercini; Kátia C Vettorello; Mariana A Porto; Renate Mohrdieck; Tani M S Ranieri; Maria T Schermann; et al. (Public Library of Science (PLoS), 2014)
In Brazil, epizootics among New World monkey species may indicate circulation of yellow fever (YF) virus and provide early warning of risk to humans. Between 1999 and 2001, the southern Brazilian state of Rio Grande do Sul initiated surveillance for epizootics of YF in non-human primates to inform vaccination of human populations. Following a YF outbreak, we analyzed epizootic surveillance data and assessed YF vaccine coverage, timeliness of implementation of vaccination in unvaccinated human populations. From October 2008 through June 2009, circulation of YF virus was confirmed in 67 municipalities in Rio Grande do Sul State; vaccination was recommended in 23 (34%) prior to the outbreak and in 16 (24%) within two weeks of first epizootic report. In 28 (42%) municipalities, vaccination began more than two weeks after first epizootic report. Eleven (52%) of 21 laboratory-confirmed human YF cases occurred in two municipalities with delayed vaccination. By 2010, municipalities with confirmed YF epizootics reported higher vaccine coverage than other municipalities that began vaccination. In unvaccinated human populations timely response to epizootic events is critical to prevent human yellow fever cases.